Performance analysis of integrated WLAN-WiMAX-UMTS networks for multimedia applications - Samundiswary, P; M, Sivasindhu (International Journal of Engineering and Technology, 2018)
Next Generation Wireless networks (NGWN) are the integration of different types of available wireless networks. These integrated networks will provide seamless connectivity for multimedia user applications. Among various wireless networks, the networks such as Wireless Local Area network (WLAN), Worldwide Interoperability for Microwave Access (WiMAX) and Universal Mobile Telecommunications System (UMTS) have their own unique characteristics and support for wide range of multimedia user applications. So, the integration of these networks and their performance analysis in respect of Quality of Service (QoS) is a major concern nowadays. Hence, this paper deals with the integration of WLAN, WiMAX and UMTS networks by considering QoS parameter. Further, the integration of these networks are analyzed with loose coupling and tight coupling architecture along with and without QoS. Furthermore, the performance analysis of the above mentioned integrated network for multimedia applications is also done. The simulation is performed through Opnet simulator.Â Â